Mineral heating cotton thread and application thereof
By using mineral heating cotton wire in electric heating products, combining cotton fibers and flexible conductors, the problems of low heating efficiency, short service life and insufficient safety of existing electric heating products are solved, and efficient heating, excellent flame retardant performance and good machinery are achieved Performance, suitable for a variety of application scenarios.
Patent Information
- Application Number
- CN202411322549.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-23
- Publication Date
- 2025-01-10
AI Technical Summary
Existing electric heating products have problems such as low heating efficiency, short service life and poor safety, especially in terms of flexibility, mechanical strength and flame retardant performance, which is difficult to meet the needs of modern consumers.
Using mineral heating cotton thread, the material consists of a cotton fiber matrix and a bonded flexible conductor, the conductive paste includes phenolic resin, allyl glycidyl ether, graphene, flame retardant and kaolin powder, through specific mixing and curing The step forms a conductor with high conductivity and flame retardant properties, bonded to the cotton fibers.
It has achieved efficient heating efficiency (99.3%~99.7%), significantly improved mechanical properties and flame retardant properties, and the limit oxygen index range is 30.9%~32.5%, which is suitable for a variety of application scenarios, including home HVAC and automotive heating systems and healthcare products.
Smart Images

Figure BDA0005054408660000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of electric heating wires, and in particular relates to a mineral heating cotton thread and an application thereof. Background Art
[0002] As people's living standards improve, the demand for heating and health care is growing. In recent years, electric heating products have been widely welcomed by the market due to their convenience, high efficiency and environmental protection. However, existing electric heating products generally have problems such as low heating efficiency, short service life and poor safety. Especially in the selection of electric heating element materials, although traditional materials such as metal wire and carbon fiber have certain conductive heating functions, they are insufficient in flexibility, mechanical strength and flame retardant properties, and it is difficult to meet the high standards of modern consumers for comfort, safety and durability.
[0003] Although metal heating wires have good conductivity, they are not suitable for applications that require frequent bending and deformation due to their strong rigidity, and are prone to breakage due to fatigue. Although carbon fiber heating materials have good flexibility and conductivity, they are relatively expensive and are prone to problems such as unstable resistance and uneven heating during long-term use, affecting the heating efficiency and user experience, and it is difficult to guarantee the service life.
[0004] In addition, with the popularization of the concept of smart home, consumers have put forward higher requirements for the safety of electric heating products. Traditional electric heating materials perform poorly in terms of flame retardancy, and once a fire accident occurs, it is easy to cause serious losses.
[0005] Therefore, the development of a new type of electric heating material that combines efficient heat generation, good flexibility, high mechanical strength and excellent flame retardant properties has become an urgent need in the industry. Summary of the invention
[0006] In view of the shortcomings of the prior art, the present invention provides a mineral heating cotton thread and its application, aiming to provide a new type of electric heating material with high efficiency heat generation, good flexibility, high mechanical strength and excellent flame retardant properties, so as to promote the widespread application of electric heating materials in various fields.
[0007] The first aspect of the present invention is to provide a mineral heating cotton thread, including a cotton fiber matrix and a flexible conductor bonded to the cotton fiber matrix; a conductive paste containing a conductive component is attached to the surface of the cotton fiber and the internal gaps, and the conductive paste is heated to solidify to form a flexible conductor bonded to the cotton fiber matrix.
[0008] Furthermore, as a further optimization scheme for the above-mentioned mineral heating cotton thread, the conductive paste includes the following components: solvent, phenolic resin, allyl glycidyl ether, N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, graphene, flame retardant, kaolin powder, and carbon powder.
[0009] Furthermore, as a further optimization scheme for the above-mentioned mineral heating cotton thread, the conductive paste is prepared by the following steps:
[0010] Step 1: uniformly mix phenolic resin and ether in a mass ratio of 2:1 to 4:1 to form a mixed solution;
[0011] Step 2: 100 parts by mass of the mixed solution prepared in step 1, 40 to 55 parts by mass of allyl glycidyl ether, 10 to 15 parts by mass of N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, 6 to 10 parts by mass of graphene dispersion, 15 to 25 parts by mass of flame retardant, 18 to 25 parts by mass of kaolin powder, and 10 to 15 parts by mass of carbon powder are uniformly mixed to obtain a primary slurry;
[0012] Step 3: Add 5 to 8 parts by weight of a catalyst and 4 to 12 parts by weight of a curing agent to the primary slurry obtained in step 2, and stir evenly to obtain a conductive slurry.
[0013] Furthermore, as a further optimization scheme for the above-mentioned mineral heating cotton thread, in step 2, the graphene dispersion is an ethanol dispersion of graphene, and the mass concentration of graphene in the dispersion is 0.8% to 2.5%.
[0014] Furthermore, as a further optimization scheme for the above-mentioned mineral heating cotton thread, in step 2, the flame retardant is ammonium polyphosphate or fluoroalkyl phosphate.
[0015] 6. According to the mineral heating cotton thread of claim 3, in step 2, the particle size of the kaolin powder is 0.2 μm to 1.5 μm, and the particle size of the carbon powder is 0.1 μm to 1.2 μm.
[0016] Furthermore, as a further optimization scheme for the above-mentioned mineral heating cotton thread, in step three, the catalyst is diethylenetriamine or triethylenetetramine, and the curing agent is hexamethylenetetramine.
[0017] Furthermore, as a further optimization solution for the above-mentioned mineral heating cotton thread, the flexible conductor combined with the cotton fiber matrix is formed by the following steps:
[0018] Step 4: Prepare clean and dry cotton fibers; immerse the cotton fibers in the conductive slurry, drain the excess conductive slurry after lifting, and air-dry in an environment below 70°C; then heat and cure at 115°C to 125°C, combine a flexible conductor on the cotton fiber matrix, and obtain mineral heating cotton thread.
[0019] In the process of preparing mineral heating cotton thread, solvent is used to dissolve other solid components to form a uniform slurry, which is convenient for subsequent mixing and coating operations; phenolic resin is used as a binder to combine the conductive slurry with cotton fibers. The three-dimensional network structure formed in the pores of the cotton fibers after curing helps to improve the overall strength and stability of the composite material, and helps to enhance the mechanical strength and durability of the mineral heating cotton thread; allyl glycidyl ether and N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane are used as cross-linking agents to improve the curing performance of the slurry, so that the final conductor is more stably and firmly bonded to the surface fibers; graphene has extremely high electrical conductivity and thermal conductivity, and is dispersed in the mineral heating cotton thread. A wide range of conductive pathways are formed in the thermal cotton thread. By adding it in the form of a dispersion, the graphene can be evenly distributed in the slurry, thereby ensuring the consistency of the heating performance. Ammonium polyphosphate or fluoroalkyl phosphate is used as a flame retardant to improve the flame retardant properties of the mineral heating cotton thread and increase its safety in use. Kaolin powder and carbon powder can improve the filling and fluidity of the slurry, and also cooperate with the resin to improve the mechanical strength and smoothness of the heating cotton thread. At the same time, the wide distribution of carbon powder further improves the conductivity of the conductor under different bending and stress conditions. The catalyst (diethylenetriamine or triethylenetetramine) and the curing agent (hexamethylenetetramine) are used to promote the curing reaction to ensure that the conductor is fully formed in the gaps and surfaces of the cotton fiber matrix. The above components in the conductive slurry cooperate with each other, so that the mineral heating cotton thread not only has excellent electrothermal conversion capabilities, but also has excellent flame retardant properties, mechanical strength, good touch and processing properties.
[0020] The second aspect of the present invention is to provide an application of the above-mentioned mineral heating cotton thread, where the mineral heating cotton thread is used to connect to a circuit. The mineral heating cotton thread has resistance. When current flows through the mineral heating cotton thread with resistance, the mineral heating cotton thread converts electrical energy into thermal energy.
[0021] Furthermore, the mineral heating cotton thread is used in home HVAC systems, vehicle heating systems or healthcare products.
[0022] Beneficial Effects
[0023] The mineral heating cotton thread provided by the present invention has many superior properties. First, its heating efficiency when powered on is as high as 99.3% to 99.7%, which means that almost all electrical energy can be efficiently converted into thermal energy, which makes it an ideal heating element that can provide sufficient heat with lower energy consumption; secondly, compared with traditional cotton fibers, the mineral heating cotton thread of the present invention exhibits significantly enhanced mechanical properties and maintains good flexibility, and its tensile strength is increased by about 90%, so it is more durable and not easy to break, and can be used in application environments that need to withstand tension, bending and friction; in addition, the mineral heating cotton thread of the present invention has excellent flame retardancy, and its limiting oxygen index ranges from 30.9% to 32.5%, and it has successfully passed the vertical burning test V-0 level, which greatly improves its safety in emergency situations such as fire, and is particularly suitable for fields such as household appliances and automotive interiors that have strict requirements on fire protection.
[0024] The mineral heating cotton thread of the present invention has the advantages of high efficiency, high strength, flame retardancy and flexibility, and shows broad application prospects in many fields such as home HVAC systems, automobile heating systems and medical care products. DETAILED DESCRIPTION
[0025] The present invention is further illustrated by specific examples below. These examples are exemplary and are intended to illustrate the problem and explain the present invention, but are not intended to be limiting.
[0026] The mineral heating cotton thread includes a cotton fiber matrix and a flexible conductor bonded to the cotton fiber matrix; a conductive paste containing a conductive component is attached to the surface of the cotton fiber and the internal gaps, and the conductive paste is heated to solidify to form a flexible conductor bonded to the cotton fiber matrix.
[0027] Example 1
[0028] Step 1: Add phenolic resin and ether in a mass ratio of 2:1 into a mixing tank and stir with a mechanical stirrer for 30 minutes until a uniform and particle-free mixture is obtained.
[0029] Step 2: Transfer 100 parts by mass of the mixed solution obtained in step 1 to a larger stirring container, add 40 parts by mass of allyl glycidyl ether, 10 parts by mass of N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, 6 parts by mass of graphene dispersion, 15 parts by mass of flame retardant, 18 parts by mass of kaolin powder, and 10 parts by mass of carbon powder in sequence, and stir at room temperature for at least 1 hour using a high-speed disperser to ensure that all ingredients are evenly dispersed to obtain a primary slurry. Among them, the graphene dispersion is an ethanol dispersion of graphene, and the mass concentration of graphene in the dispersion is 1.5%; the flame retardant is ammonium polyphosphate; the particle size of the kaolin powder is 0.2μm to 1.5μm, and the particle size of the carbon powder is 0.1μm to 1.2μm.
[0030] Step 3: Add 5 parts by mass of a catalyst and 4 parts by mass of a curing agent to the primary slurry obtained in step 2. Continue stirring until all components are evenly dispersed in the system to form a uniform conductive slurry. The catalyst is diethylenetriamine and the curing agent is hexamethylenetetramine.
[0031] Step 4: Prepare clean and dry cotton fibers and immerse them in the prepared conductive slurry to ensure that the fibers are completely soaked. Subsequently, lift the soaked cotton fibers and gently squeeze to remove excess slurry. Then, hang the cotton fibers in a 65°C air drying oven to air dry for 24 hours. Then, place the air-dried cotton fibers in an oven preheated to 120°C for heating and curing for 6 hours until a stable conductive layer is formed on the surface of the cotton fibers to obtain the final mineral heating cotton thread.
[0032] Example 2
[0033] Step 1: Add phenolic resin and ether in a mass ratio of 3:1 into a mixing tank and stir with a mechanical stirrer for 30 minutes until a uniform and particle-free mixture is obtained.
[0034] Step 2: Transfer 100 parts by mass of the mixed solution obtained in step 1 to a larger stirring container, add 48 parts by mass of allyl glycidyl ether, 12 parts by mass of N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, 7 parts by mass of graphene dispersion, 12 parts by mass of flame retardant, 22 parts by mass of kaolin powder, 10 parts by mass of carbon powder, and stir at room temperature for at least 1 hour using a high-speed disperser to ensure that all ingredients are evenly dispersed to obtain a primary slurry. Among them, the graphene dispersion is an ethanol dispersion of graphene, and the mass concentration of graphene in the dispersion is 1.5%; the flame retardant is ammonium polyphosphate; the particle size of the kaolin powder is 0.2μm to 1.5μm, and the particle size of the carbon powder is 0.1μm to 1.2μm.
[0035] Step 3: Add 6 parts by mass of a catalyst and 8 parts by mass of a curing agent to the primary slurry obtained in step 2. Continue stirring until all components are evenly dispersed in the system to form a uniform conductive slurry. The catalyst is diethylenetriamine and the curing agent is hexamethylenetetramine.
[0036] Step 4: Prepare clean and dry cotton fibers and immerse them in the prepared conductive slurry to ensure that the fibers are completely soaked. Subsequently, lift the soaked cotton fibers and gently squeeze to remove excess slurry. Then, hang the cotton fibers in a 65°C air drying oven to air dry for 24 hours. Then, place the air-dried cotton fibers in an oven preheated to 120°C for heating and curing for 6 hours until a stable conductive layer is formed on the surface of the cotton fibers to obtain the final mineral heating cotton thread.
[0037] Example 3
[0038] Step 1: Add phenolic resin and ether in a mass ratio of 3:1 into a mixing tank and stir with a mechanical stirrer for 30 minutes until a uniform and particle-free mixture is obtained.
[0039] Step 2: Transfer 100 parts by mass of the mixed solution obtained in step 1 to a larger stirring container, add 52 parts by mass of allyl glycidyl ether, 12 parts by mass of N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, 9 parts by mass of graphene dispersion, 23 parts by mass of flame retardant, 22 parts by mass of kaolin powder, and 13 parts by mass of carbon powder in sequence, and stir at room temperature for at least 1 hour using a high-speed disperser to ensure that all ingredients are evenly dispersed to obtain a primary slurry. Among them, the graphene dispersion is an ethanol dispersion of graphene, and the mass concentration of graphene in the dispersion is 1.5%; the flame retardant is ammonium polyphosphate; the particle size of the kaolin powder is 0.2μm to 1.5μm, and the particle size of the carbon powder is 0.1μm to 1.2μm.
[0040] Step 3: Add 6 parts by mass of a catalyst and 8 parts by mass of a curing agent to the primary slurry obtained in step 2. Continue stirring until all components are evenly dispersed in the system to form a uniform conductive slurry. The catalyst is diethylenetriamine and the curing agent is hexamethylenetetramine.
[0041] Step 4: Prepare clean and dry cotton fibers and immerse them in the prepared conductive slurry to ensure that the fibers are completely soaked. Subsequently, lift the soaked cotton fibers and gently squeeze to remove excess slurry. Then, hang the cotton fibers in a 65°C air drying oven to air dry for 24 hours. Then, place the air-dried cotton fibers in an oven preheated to 120°C for heating and curing for 6 hours until a stable conductive layer is formed on the surface of the cotton fibers to obtain the final mineral heating cotton thread.
[0042] Example 4
[0043] Step 1: Add phenolic resin and ether in a mass ratio of 3:1 into a mixing tank and stir with a mechanical stirrer for 30 minutes until a uniform and particle-free mixture is obtained.
[0044] Step 2: Transfer 100 parts by mass of the mixed solution obtained in step 1 to a larger stirring container, add 53 parts by mass of allyl glycidyl ether, 11 parts by mass of N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, 9 parts by mass of graphene dispersion, 17 parts by mass of flame retardant, 25 parts by mass of kaolin powder, and 15 parts by mass of carbon powder in sequence, and stir at room temperature for at least 1 hour using a high-speed disperser to ensure that all ingredients are evenly dispersed to obtain a primary slurry. Among them, the graphene dispersion is an ethanol dispersion of graphene, and the mass concentration of graphene in the dispersion is 1.5%; the flame retardant is a fluoroalkyl phosphate; the particle size of the kaolin powder is 0.2μm to 1.5μm, and the particle size of the carbon powder is 0.1μm to 1.2μm.
[0045] Step 3: Add 6 parts by mass of a catalyst and 8 parts by mass of a curing agent to the primary slurry obtained in step 2. Continue stirring until all components are evenly dispersed in the system to form a uniform conductive slurry. The catalyst is triethylenetetramine and the curing agent is hexamethylenetetramine.
[0046] Step 4: Prepare clean and dry cotton fibers and immerse them in the prepared conductive slurry to ensure that the fibers are completely soaked. Subsequently, lift the soaked cotton fibers and gently squeeze to remove excess slurry. Then, hang the cotton fibers in a 65°C air drying oven to air dry for 24 hours. Then, place the air-dried cotton fibers in an oven preheated to 120°C for heating and curing for 6 hours until a stable conductive layer is formed on the surface of the cotton fibers to obtain the final mineral heating cotton thread.
[0047] Example 5
[0048] Step 1: Add phenolic resin and ether in a mass ratio of 3:1 into a mixing tank and stir with a mechanical stirrer for 30 minutes until a uniform and particle-free mixture is obtained.
[0049] Step 2: Transfer 100 parts by mass of the mixed solution obtained in step 1 to a larger stirring container, add 49 parts by mass of allyl glycidyl ether, 13 parts by mass of N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, 9 parts by mass of graphene dispersion, 22 parts by mass of flame retardant, 23 parts by mass of kaolin powder, and 13 parts by mass of carbon powder in sequence, and stir at room temperature for at least 1 hour using a high-speed disperser to ensure that all ingredients are evenly dispersed to obtain a primary slurry. Among them, the graphene dispersion is an ethanol dispersion of graphene, and the mass concentration of graphene in the dispersion is 1.5%; the flame retardant is a fluoroalkyl phosphate; the particle size of the kaolin powder is 0.2μm to 1.5μm, and the particle size of the carbon powder is 0.1μm to 1.2μm.
[0050] Step 3: Add 6 parts by mass of a catalyst and 8 parts by mass of a curing agent to the primary slurry obtained in step 2. Continue stirring until all components are evenly dispersed in the system to form a uniform conductive slurry. The catalyst is triethylenetetramine and the curing agent is hexamethylenetetramine.
[0051] Step 4: Prepare clean and dry cotton fibers and immerse them in the prepared conductive slurry to ensure that the fibers are completely soaked. Subsequently, lift the soaked cotton fibers and gently squeeze to remove excess slurry. Then, hang the cotton fibers in a 65°C air drying oven to air dry for 24 hours. Then, place the air-dried cotton fibers in an oven preheated to 120°C for heating and curing for 6 hours until a stable conductive layer is formed on the surface of the cotton fibers to obtain the final mineral heating cotton thread.
[0052] Example 6
[0053] Step 1: Add phenolic resin and ether in a mass ratio of 4:1 into a mixing tank and stir with a mechanical stirrer for 30 minutes until a uniform and particle-free mixture is obtained.
[0054] Step 2: Transfer 100 parts by mass of the mixed solution obtained in step 1 to a larger stirring container, add 55 parts by mass of allyl glycidyl ether, 15 parts by mass of N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, 10 parts by mass of graphene dispersion, 25 parts by mass of flame retardant, 25 parts by mass of kaolin powder, and 15 parts by mass of carbon powder in sequence, and stir at room temperature for at least 1 hour using a high-speed disperser to ensure that all ingredients are evenly dispersed to obtain a primary slurry. Among them, the graphene dispersion is an ethanol dispersion of graphene, and the mass concentration of graphene in the dispersion is 1.5%; the flame retardant is a fluoroalkyl phosphate; the particle size of the kaolin powder is 0.2μm to 1.5μm, and the particle size of the carbon powder is 0.1μm to 1.2μm.
[0055] Step 3: Add 8 parts by mass of a catalyst and 12 parts by mass of a curing agent to the primary slurry obtained in step 2. Continue stirring until all components are evenly dispersed in the system to form a uniform conductive slurry. The catalyst is triethylenetetramine and the curing agent is hexamethylenetetramine.
[0056] Step 4: Prepare clean and dry cotton fibers and immerse them in the prepared conductive slurry to ensure that the fibers are completely soaked. Subsequently, lift the soaked cotton fibers and gently squeeze to remove excess slurry. Then, hang the cotton fibers in a 65°C air drying oven to air dry for 24 hours. Then, place the air-dried cotton fibers in an oven preheated to 120°C for heating and curing for 6 hours until a stable conductive layer is formed on the surface of the cotton fibers to obtain the final mineral heating cotton thread.
[0057] Test Case
[0058] The samples prepared in the embodiment were tested for performance. The tensile strength was tested with reference to GB / T2951-2008 General Test Method for Insulation and Sheath Materials of Electric Cables and Optical Cables. The change rate of tensile strength = (tensile strength of mineral heating cotton thread - tensile strength of cotton fiber) / tensile strength of cotton fiber × 100%; the limiting oxygen index test (LOI) was tested with reference to ASTM D2863 / 77; the vertical burning test (UL-94) was tested with reference to ASTM (D63-77); the heating efficiency was tested with reference to GB / T 29313-2012 Test Method for Thermal Conductivity of Electrical Insulation Materials. The test results are shown in Table 1.
[0059] Table 1 Performance test results
[0060]
[0061] The results show that the mineral heating cotton thread samples prepared in the embodiment not only have excellent electrical heating performance compared to the cotton fiber matrix, but also have significantly improved tensile strength and flame retardant properties. Compared with the cotton fiber matrix, the change rate of the tensile strength of the mineral heating cotton thread can reach about 90%, the vertical combustion test level reaches V-0, the limiting oxygen index reaches 30.9% to 32.5%, and it also has extremely high heating efficiency, with a heating efficiency of 99.3% to 99.7%.
[0062] Based on the excellent performance of the above-mentioned mineral heating cotton thread, it has good application prospects and significant advantages in many scenarios.
[0063] For example, in home HVAC systems, mineral heating cotton threads can be used in home heating equipment such as electric blankets and floor heating systems. Due to its extremely high heating efficiency (99.3% to 99.7%), almost all electrical energy can be converted into thermal energy, which helps to reduce energy consumption and save usage costs. In addition, mineral heating cotton threads have excellent flame retardant properties (V-0 grade), which can ensure the safety of users even in unexpected situations. The significantly improved tensile strength makes the fiber durable and not easy to damage, which helps to extend the service life of the product.
[0064] For example, in the car heating system, mineral heating cotton can be used for car seat heating, steering wheel heating and other components. Mineral heating cotton can not only heat up quickly, but also adapt well to the shape of the seat and steering wheel due to the flexibility of the material itself, providing uniform heat distribution. The excellent flame retardant properties and high oxygen index also make it safer and more reliable when used in the car.
[0065] For example, in healthcare products, mineral heating cotton can be used in products such as electric heating therapy pads and warm clothing. The high heating efficiency enables it to quickly reach the temperature required for treatment, thereby accelerating blood circulation and relieving muscle pain. At the same time, the excellent mechanical properties ensure that the material can still work normally after multiple bends, which is especially important for medical supplies that often need to be washed and reused. In addition, its flame retardant properties also make such products safer during use.
[0066] The above embodiments are exemplary, and their purpose is to illustrate the technical concept and features of the present invention so that people familiar with the technology in this field can understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.
Claims
1. A mineral heating cotton thread, characterized in that: The invention comprises a cotton fiber matrix and a flexible conductor combined with the cotton fiber matrix; a conductive paste containing conductive components is attached to the surface of the cotton fiber and the internal gaps, and the conductive paste is heated to solidify to form the flexible conductor combined with the cotton fiber matrix.
2. The mineral heating cotton thread according to claim 1, characterized in that: The conductive paste comprises the following components: a solvent, a phenolic resin, allyl glycidyl ether, N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, graphene, a flame retardant, kaolin powder and carbon powder.
3. The mineral heating cotton thread according to claim 1, characterized in that: The conductive paste is prepared by the following steps: Step 1: uniformly mix phenolic resin and ether in a mass ratio of 2:1 to 4:1 to form a mixed solution; Step 2: 100 parts by mass of the mixed solution prepared in step 1, 40-55 parts by mass of allyl glycidyl ether, 10-15 parts by mass of N,N,N',N'-tetraglycidyl-4,4'-diaminodiphenylmethane, 6-10 parts by mass of graphene dispersion, 15-25 parts by mass of flame retardant, 18-25 parts by mass of kaolin powder, and 10-15 parts by mass of carbon powder are uniformly mixed to obtain a primary slurry; Step 3: Add 5 to 8 parts by weight of a catalyst and 4 to 12 parts by weight of a curing agent to the primary slurry obtained in step 2, and stir evenly to obtain a conductive slurry.
4. The mineral heating cotton thread according to claim 3, characterized in that: In step 2, the graphene dispersion is an ethanol dispersion of graphene, and the mass concentration of graphene in the dispersion is 0.8% to 2.5%.
5. The mineral heating cotton thread according to claim 3, characterized in that: In step 2, the flame retardant is ammonium polyphosphate or fluoroalkyl phosphate.
6. The mineral heating cotton thread according to claim 3, characterized in that: In step 2, the particle size of the kaolin powder is 0.2 μm to 1.5 μm, and the particle size of the carbon powder is 0.1 μm to 1.2 μm.
7. The mineral heating cotton thread according to claim 3, characterized in that: In step three, the catalyst is diethylenetriamine or triethylenetetramine, and the curing agent is hexamethylenetetramine.
8. The mineral heating cotton thread according to claim 1, characterized in that: The flexible conductor bonded to the cotton fiber matrix is formed using the following steps: Step 4: Prepare clean and dry cotton fibers; immerse the cotton fibers in the conductive slurry, drain the excess conductive slurry after lifting them up, and place them in an environment below 70° C. to air dry; Then, the mineral heating cotton thread is obtained by heating and curing at 115° C. to 125° C., and combining a flexible conductor on the cotton fiber matrix.
9. The use of the mineral heating cotton thread according to any one of claims 1 to 8, characterized in that: The mineral heating cotton thread is used to be connected to a circuit. The mineral heating cotton thread has resistance. When current flows through the mineral heating cotton thread with resistance, the mineral heating cotton thread converts electrical energy into thermal energy.
10. The use of the mineral heating cotton thread according to claim 10, characterized in that: The mineral heating cotton thread is used in home heating and ventilation systems, vehicle heating systems or health care products.